Respiratory symptoms and inflammatory responses to Difflam throat-spray intervention in half-marathon runners: a randomised controlled trial. Issue 2 (3rd June 2008) - Cox, A J; Gleeson, M; Pyne, D B; Saunders, P U; Callister, R; Fricker, P A
Abstract : Objective: In this study, the effects of Difflam Forte Anti-inflammatory Throat Spray on the incidence of upper respiratory symptoms (URS) and inflammatory responses after a half-marathon race were investigated. Design and setting: Double-blind placebo-controlled randomised trial conducted in association with a half-marathon event. Participants: 45 well-trained half-marathon runners. Interventions: Difflam (n = 25) or placebo (n = 20) throat sprays were self-administered three times daily for 1 week before and 2 weeks after the race. Main outcome measures: Self-reported respiratory symptoms; plasma prostaglandin E2, myeloperoxidase, interleukin (IL) 6, IL8, IL10 and IL1 receptor antagonist (IL1ra) concentrations; and salivary myeloperoxidase and IL6 concentrations. Results: All subjects completed the intervention without reporting any adverse events. The proportion of athletes reporting URS was not substantially different between Difflam (52%) and placebo (56%) groups (p = 0.82). However, symptom severity scores were ∼29% lower during Difflam treatment (4.7 (7.4) vs 6.6 (9.6)) AU). Post-exercise responses in plasma inflammatory markers did not differ substantially between Difflam and placebo groups. Post-race increases in salivary myeloperoxidase (∼63%; trivial to moderate difference; p = 0.13) and salivary IL6 (∼50%; trivial to moderate difference; p = 0.25) were greater in the Difflam group. Conclusions: Prophylactic use of the Difflam reduced the severity, but not the frequency, of URS among half-marathon runners. Post-race increases in systemic inflammatory markers were not altered by Difflam use, but markers of local inflammation (salivary myeloperoxidase and IL6) were augmented in the Difflam compared with the placebo group.